Project Report on Optimization of a Product Lifecycle Management Tool - ANGUS CYPRIYAN MONIERO, SIDDHARTH G, ANEEZ A V and GEETHA N (2010)
INTERNAL GUIDE: VARADARAJ K R, MVJCE EXTERNAL GUIDE: RAMKUMAR D, OPERATION MANAGER, E-RING SOFTWARE SOLUTION BANGALORE
Keywords: Product Lifecycle Management Tool